An extended model of the theory of planned behaviour to predict purchase intention for local brand vehicles produced in Malaysia - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Hashim, Ahmad Hariza; Ho, Jo Ann (Human Resource Management Academic Research Society, 2023)
The single-digit growth rate of the Malaysian Automotive sector has experienced a slight decline elicited by Covid-19 and a change in consumers product evaluation criteria. This necessitates an inclusive business model that encompasses consumers interests and organisational goals through the extension of the Theory of Planned Behaviour with consumer corporate identification (CCI). Using a sample of 373 potential consumers of Proton vehicles in Malaysia, a quantitative study that utilised AMOS graphics version 24 was conducted to predict purchase intention for Proton vehicles produced in Malaysia. The results showed that collectivism and consumer ethnocentrism (CE) explained 44.3 variance in attitude towards purchase intention, whereas the entire model (attitude, collectivism, CE, subjective norm, perceived behavioural control (PBC), and CCI) explained 61.3 variance in purchase intention for Proton vehicles. CE significantly influenced attitudes toward purchase intention more than collectivism. Subjective norm significantly predicted purchase intention for Proton vehicles more than CCI, attitude, and PBC. In a collectivistic society, purchase intention for local products may not be realised without substantial attention to consumers subjective norms, and CE. Local brand manufacturers should pay attention to previous purchasers evaluations of local brands to ensure a positive word-of-mouth strategy because they may incidentally be among potential consumers social circles. Marketers of local brand vehicles should embark on programs that enhance CE to sustain favourable attitudes toward purchase intention for their products. The study demonstrated the importance of a common identity between consumers and firms through CCI implementation and its implications for purchase intention.